Degradation of catalytic epoxidation of oleic acid palm oil by in situ performic acid / Nurul Fathiah Wahi, Mohd Jumain Jalil and Aliff Farhan Mohd Yamin - Wahi, Nurul Fathiah; Jalil, Mohd Jumain; Mohd Yamin, Aliff Farhan (2020)
The world consumption of raw material has been changing from a non-renewable material into a renewable material. The study on the epoxidation has also changed in a much cost-effective and a greener product which is safer than the non-renewable material. The increasing study of vegetable oil has been in demand. Epoxidation of oleic acid was carried out by in situ performic acid to produce epoxidized oleic acid. Since epoxide ring is highly reactive, the degradation of the oxirane was tested by using hydrogen peroxide, formic acid and water. The degradation of the epoxide is mainly focus on the production of DHSA. Therefore, the study on degradation of the epoxide is lacking. Analysis by using FTIR and NMR are conducted to know the characterization of the degradation product. As a result, the degradation is highly effective in an acidic condition such as hydrogen peroxide and formic acid which lead to a formation of side products such as diol and α-glycol (carboxylic acid). Then, the kinetic rate, k parameters obtained by using an ODE45 function on MATLAB software is k11= 6.6442, k12= 11.0185, k21= 0.1026, for epoxidation palm oleic acid, and k31 = 0.0347, k41= 0.0154, k51= 0.0142, in degradation process. The minimum error of the simulation is 0.17311.